Impact and Causes of Early Marriage in Adolescents: Systematic Review - Ani Nurhaeni; Dewi Erna Marisa; Thia Oktiany; Rosalia Rahayu; Lili Wahyuni (Malahayati Nursing Journal, 2025)
ABSTRACT Early marriage remains a persistent global issue, particularly affecting adolescent girls in low-resource settings. It has far-reaching implications, including health risks, disrupted education, and socio-economic challenges. This systematic literature review aims to analyze the impacts and causes of early marriage among adolescent girls, focusing on health, education, and socio-economic consequences, while identifying evidence-based interventions to address the issue.  The study uses a systematic literature review (SLR) approach, following the PRISMA framework for article selection and inclusion. Articles published between 2019–2024 were analyzed using thematic synthesis. Results: Early marriage significantly impacts adolescent girls' health, including pregnancy complications, perinatal mortality, and mental health issues like anxiety and depression. Educationally, it causes school dropouts, limiting skills and future employment opportunities. Socio-economic factors, such as poverty and cultural norms, were found to be primary drivers. Rural and marginalized communities face higher prevalence due to limited access to education and healthcare services.  Addressing early marriage requires holistic, multi-sectoral interventions, including improving education access, empowering girls economically, challenging cultural norms, and promoting gender equality.  Keyword: Early Marriage, Adolescent Girls, Health and Education Impact, Gender Inequality  ABSTRAK Pernikahan dini tetap menjadi permasalahan global yang terus berlangsung, terutama berdampak pada remaja perempuan di daerah dengan sumber daya terbatas. Masalah ini memiliki implikasi yang luas, termasuk risiko kesehatan, terganggunya pendidikan, serta tantangan sosial dan ekonomi. Tinjauan literatur sistematis ini bertujuan untuk menganalisis dampak dan penyebab pernikahan dini pada remaja perempuan, dengan fokus pada aspek kesehatan, pendidikan, dan konsekuensi sosial-ekonomi, serta mengidentifikasi intervensi berbasis bukti untuk mengatasi permasalahan tersebut. Studi ini menggunakan pendekatan systematic literature review (SLR), dengan mengikuti kerangka kerja PRISMA dalam proses seleksi dan inklusi artikel. Artikel yang diterbitkan antara tahun 2019–2024 dianalisis menggunakan sintesis tematik. Pernikahan dini secara signifikan berdampak pada kesehatan remaja perempuan, termasuk komplikasi kehamilan, kematian perinatal, serta masalah kesehatan mental seperti kecemasan dan depresi. Dalam bidang pendidikan, pernikahan dini menyebabkan putus sekolah yang membatasi keterampilan dan peluang kerja di masa depan. Faktor sosial-ekonomi seperti kemiskinan dan norma budaya ditemukan sebagai penyebab utama. Komunitas pedesaan dan kelompok marjinal memiliki prevalensi lebih tinggi akibat keterbatasan akses terhadap pendidikan dan layanan kesehatan. Penanganan pernikahan dini memerlukan intervensi holistik dan lintas sektor, termasuk peningkatan akses pendidikan, pemberdayaan ekonomi bagi perempuan, perubahan norma budaya, dan promosi kesetaraan gender. Kata Kunci: Pernikahan Dini, Remaja Perempuan, Dampak Kesehatan dan Pendidikan, Ketimpangan Gender.